THE INFLUENCE OF CAPITAL STRUCTURE, COMPANY SIZE AND CASH ROUND TOWARDS PROFITABILITY OF METAL SUB-SECTOR MANUFACTURING COMPANIES AND THEIR SECTORS LISTED IN INDONESIA STOCK EXCHANGE 2016-2018 - Putri Nurhaliza; Rahmawati Rahmawati; Rani Munika (STIE Bangkinang Publishing, 2021)
The purpose of this study was to determine the effect of Capital Structure (DER), Company Size (size) and Cash Turnover (CT) on Profitability (ROA) in Metal Manufacturing Companies and the like listed on the Indonesia Stock Exchange (BEI) 2016-2018 period. The population and sample in this study were all metal sub-sector manufacturing companies and the like listed on the Indonesia Stock Exchange in 2016-2018, as many as 15 companies. The technique used in sampling is the census method, the results of hypothesis testing using multiple linear regression analysis with the help of SPSS 25.00 for windows. The results of the study Capital Structure (DER), Company Size (size) and Cash Turnover (CT) affect profitability (ROA). Meanwhile, partially, the variable that affects profitability is Cash Turnover (CT).